Growth of oriented single crystalline La-doped TiO2 nanorod arrays electrode and investigation of optoelectronic properties for enhanced photoelectrochemical activity - Sadhu, Subha; Poddar, Pankaj (RSC Advances, 2013)
Fabrication of single crystalline, oriented one-dimensional (1D) rods or wires of titania on transparent conducting oxide (TCO) substrates have enormous significance in the area of photoelectrochemical research owning to their unique optoelectronic properties. It is possible to modify the electrical conductivity and optoelectronic properties of titania by intentional inclusion of atomic impurity in the material. Here for the first time, we have doped lanthanum homogeneously in TiO2 nanorod arrays. The homogeneous distribution of lanthanum in titania lattice is confirmed by scanning transmission electron microscopy (STEM) elemental mapping and line scanning analysis. After doping with lanthanum, there is a negative shift of the flat-band potential of the TiO2 nanorods and the charge carrier density of the nanorods is also improved. The energy-conversion efficiency of a dye-sensitized solar cell based on 4 mol% La-doped nanorods is increased about 21% compared with the undoped one.